(3a-3)(4a-5)=

Simple and best practice solution for (3a-3)(4a-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3a-3)(4a-5)= equation:


Simplifying
(3a + -3)(4a + -5) = 0

Reorder the terms:
(-3 + 3a)(4a + -5) = 0

Reorder the terms:
(-3 + 3a)(-5 + 4a) = 0

Multiply (-3 + 3a) * (-5 + 4a)
(-3(-5 + 4a) + 3a * (-5 + 4a)) = 0
((-5 * -3 + 4a * -3) + 3a * (-5 + 4a)) = 0
((15 + -12a) + 3a * (-5 + 4a)) = 0
(15 + -12a + (-5 * 3a + 4a * 3a)) = 0
(15 + -12a + (-15a + 12a2)) = 0

Combine like terms: -12a + -15a = -27a
(15 + -27a + 12a2) = 0

Solving
15 + -27a + 12a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '3'.
3(5 + -9a + 4a2) = 0

Factor a trinomial.
3((1 + -1a)(5 + -4a)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(1 + -1a)' equal to zero and attempt to solve: Simplifying 1 + -1a = 0 Solving 1 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = 0 + -1 -1a = 0 + -1 Combine like terms: 0 + -1 = -1 -1a = -1 Divide each side by '-1'. a = 1 Simplifying a = 1

Subproblem 2

Set the factor '(5 + -4a)' equal to zero and attempt to solve: Simplifying 5 + -4a = 0 Solving 5 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4a = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4a = 0 + -5 -4a = 0 + -5 Combine like terms: 0 + -5 = -5 -4a = -5 Divide each side by '-4'. a = 1.25 Simplifying a = 1.25

Solution

a = {1, 1.25}

See similar equations:

| 5(4+c)=4(c-4) | | y+x=3 | | 3y-2(18)=3 | | 5-4x=19+3x | | -4n+13=-3n-10 | | -2Y-12=5Y+30 | | 5Y-7=2Y+2 | | -7(5v-u-3)= | | (6x^2-16x+33)=0 | | (5w-15)(15w-5)=0 | | -4+15=14x-3-13x | | 4(8-w)= | | (4t+9)(t+8)=0 | | 8y-14y=-24-30 | | 8(x+4)=2(4x+5)+22 | | m-7m-5m+9= | | 5y-4x=20 | | 12(3x+3)-7(2x-7)=2x-55 | | -5-(-12)=X | | 2-b=23 | | x^3+4x^2-25x-100=0 | | 12x-5(x-6)=7x+5 | | 4(4c-1)-2=14c+2 | | 8(3x-2)=4(6x+9) | | -3(t+1)=12 | | 2.5x+10=7.5 | | -2x-6=-22 | | -78=-30+6x | | 2(2x+8)=2(3x+6) | | 33-18=3(x-2) | | 2x^4-7x^3+14x^2-28x+24=0 | | 24+5y-7=16y-10-2y |

Equations solver categories